Looking for optimal antithrombotic strategy after transcatheter left atrial appendage occlusion: a real-world comparison of different antiplatelet regimens. (15th January 2023) - Vignali, Luigi; Gurgoglione, Filippo Luca; Barocelli, Federico; Cattabiani, Maria Alberta; Solinas, Emilia; Maini, Arianna; Tadonio, Iacopo; Benatti, Giorgio; Pelà, Giovanna; Coli, Stefano; Ardissino, Diego; Niccoli, Giampaolo
Abstract: Background: Transcatheter left atrial appendage occlusion (LAAO) has emerged as an effective procedure for the prevention of thromboembolic events in non-valvular atrial fibrillation (AF) patients with contraindications to oral anticoagulation. After the procedure, different antithrombotic regimens have been used, in order to prevent device-related thrombus and trying to minimize bleedings. The search for the optimal antithrombotic strategy is still ongoing. We sought to assess efficacy and safety of different antiplatelet therapy (APT) regimens. Methods: We enrolled non-randomized consecutive patients who underwent LAAO at the University Hospital of Parma between 2010 and 2021. Three study groups were identified according to post-procedural APT: long (>1, ≤12 months)-dual APT (DAPT), short (≤ 1 month)-DAPT, lifelong single APT (SAPT). The choice of the APT was left to multidisciplinary team evaluation. The incidence of the primary outcome, a composite of any ischemic or hemorrhagic event, was assessed at follow-up. Results: We enrolled a total of 130 patients. Technical success was achieved in 123 (94.6%) patients. After LAAO, 39 [31.7%] patients were discharged on short-DAPT, 35 [28.5%] on long-DAPT and 49 [39.8%] on SAPT. After a median follow-up of 32 months, short-DAPT group had a significantly lower occurrence of the primary outcome (3 [7.7%] vs. 7 [20.0%] in long-DAPT vs. 14 [28.6%] in SAPT, p = 0.049], mainly driven by a lower occurrence of the bleeding endpoint (0 vs. 4 [11.4%] in long-DAPT vs. 9 [18.4%] in SAPT, p = 0.020). Finally, comparison of the Kaplan-Meier curves showed that short-DAPT group had a higher primary endpoint-free survival [ p = 0.015] compared to the other groups. Conclusion: Post-procedural short-DAPT strategy was associated with better outcomes, mainly driven by reduction of major bleedings. Graphical abstract: Graphical summary of the study design and results. Abbreviations: DRT: Device-Related Thrombus; LAAO: Left Atrial Appendage Occlusion; SAPT: Single Anti-Platelet Therapy; DAPT: Dual Anti-Platelet Therapy; SE: Systemic Embolism; TIA: Transient Ischemic Attack. Unlabelled Image Highlights: Antithrombotic therapy after left atrial appendage occlusion remains an open question. Comparing to long dual antiplatelet therapy (DAPT) and single APT, short DAPT was associated with better outcome. Continuous single antiplatelet therapy is related to more bleeding rates. A multidisciplinary team evaluation is essential to devise a personalized approach.